COVID-19 Policy Response (CPR) portal - Resnick, Danielle; Prasai, Nilam (International Food Policy Research Institute, 2020)
The spread of COVID-19, and the range of policy responses to contain the pandemic, exert wide-ranging effects on agri-food systems and livelihoods. To analyze the direct and indirect impacts of these responses in a comparative way, the COVID-19 Policy Response (CPR) Portal systematically captures policy responses through multiple channels, including population restrictions, social protection, trade, health, fiscal, and monetary measures. The Portal also examines the different types of institutional collaboration governments have used to manage the pandemic, as well as different degrees of citizen compliance. Many responses to COVID-19 have centered on cities or have been spatially differentiated in federal and more devolved country settings. Consequently, CPR includes details at the subnational level as well where relevant. The CPR is being led by IFPRI’s country and regional programs and supported by the Food Security Group of Michigan State University and by national institutions across the world. By bringing together the insights from existing policy initiatives as well as in-depth knowledge from our experts in-country, we hope to offer information for governments, donors, and researchers about which policies best work for fostering resilience and keeping food systems working during crises. The full dataset will be regularly updated.